Protein Targeting Protocols - van der Giezen, Mark.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
In this highly anticipated update of the extremely successful Protein Targeting Protocols, experts from around the world provide the latest protocols on for isolating different organelles and the localization of particular proteins using a variety of methods such as light, confocal, and electron microscopy. Unlike the first edition, however, this volume places emphasis on protein targeting of cellular compartments in both prokaryotic and eukaryotic systems. Authors provide state-of-the-art information on the fast moving fields of import machinery of mitochondria and plastids, as well as a detailed protocol on the movement of protein complexes in bacterial membranes using fluorescent recovery after photobleaching. Bacterial protein targeting protocols using the Sec-system, type-V secretion apparatus, and the Tat-pathway are described, as is a periplasmic targeting protocol. Chapters also include bioinformatics methods to guide readers through the ever-increasing number of in silico tools currently available. Editor Mark van der Giezen has succeeded in including targeting protocols from different systems, including animal, plant, fungal, and protist models, providing insights into the intricate challenges presented by these diverse systems. Authoritative and state-of-the-art, Protein Targeting Protocols, Second Edition, provides useful techniques that will aid scientists working with a variety of organisms.
Bacterial Systems -- Localization and Mobility of Bacterial Proteins by Confocal Microscopy and Fluorescence Recovery After Photobleaching -- Membrane Protein Insertion and Secretion in Bacteria -- Identification of Autotransporter Proteins Secreted by Type V Secretion Systems in Gram-Negative Bacteria -- Periplasmic Targeting of Recombinant Proteins in Escherichia coli -- In Vitro Analysis of the Bacterial Twin-Arginine-Dependent Protein Export -- Eukaryotic Systems -- Nuclear Import Properties of the Sex-Determining Factor SRY -- The Mitochondrial Machinery for Import of Precursor Proteins -- A Genetic Method to Identify Mitochondrial Proteins in Living Mammalian Cells -- In Vitro and In Vivo Methods to Study Protein Import Into Plant Mitochondria -- Protein Targeting to Mitochondria of Saccharomyces cerevisiae and Neurospora crassa -- A Mitosome Purification Protocol Based on Percoll Density Gradients and Its Use in Validating the Mitosomal Nature of Entamoeba histolytica Mitochondrial Hsp70 -- The Chloroplast Protein Import Machinery: A Review -- Import of Plastid Precursor Proteins Into Pea Chloroplasts -- Protein Targeting in ‘‘Secondary’’ or ‘‘Complex’’ Chloroplasts -- Protein Trafficking to the Complex Chloroplasts of Euglena -- Fluorescent Protein Fusions for Protein Localization in Plants -- Genetic Transformation -- Identification of Proteins Targeted Into the Endoplasmic Reticulum by cDNA Library Screening -- Trafficking Through the Early Secretory Pathway of Mammalian Cells -- Studying Protein Export From the Endoplasmic Reticulum in Plants -- Imaging the Golgi Apparatus in Living Mitotic Cells -- Evaluating Yeast Biosynthetic Vacuolar Transport -- Targeting to Lysosomes in Mammalian Cells -- Monitoring Autophagy in Yeast -- Protein Targeting to Yeast Peroxisomes -- Expression, Localization, and Topology of Fluorescently Tagged Plasma Membrane-Targeted Transmembrane Proteins -- General Methods -- Intracellular Protein Localization by Immunoelectron Microscopy -- Separation of Proteins by Blue Native Electrophoresis -- Computational Prediction of Subcellular Localization -- Phylogenetic Analysis to Uncover Organellar Origins of Nuclear-Encoded Genes.
Keywords: Proteins .; Cell biology; Human genetics; Protein Science; Cell Biology; Human Genetics